PERENCANAAN STRATEGIS SISTEM INFORMASI DI PT TELEKOMUNIKASI INDONESIA, Tbk WITEL SEMARANG MENGGUNAKAN WARD AND PEPPARD - Adi Wiyono; Agustinus Fritz Wijaya (Jurnal Ilmiah Terpadu Universitas Bina Darma, 2020)
PT Telekomunikasi Indonesia is a State-Owned Enterprise (BUMN) engaged in the field of communication information technology services and telecommunications networks in Indonesia. In running its business, PT Telekomunikasi Indonesia has used technology to run its business. PT Telekomunikasi Indonesia has several divisions that are ready to work in accordance with existing procedures. It is expected that the existence of Human Resources (HR) that is owned now can provide added value to the company PT. Telekomunikasi Indonesia Witel Semarang. The current Human Resources, in the use of technology at PT Telekomunikasi Indonesia Witel Semarang is still not optimal. Given this problem, this research was made using the Ward and Peppard method, with several analytical techniques using PEST and Value Chain techniques to analyze the internal and external environment of the business, SWOT to analyze the internal and external environments of SI and IT, and McFarlan Strategic Grid for mapping application portfolio. This research is expected to improve performance or service for customers in accordance with the company's business goals.